Near‐infrared spectroscopy for intracoronary detection of lipid‐rich plaques to understand atherosclerotic plaque biology in man and guide clinical therapy. (19th June 2015) - Erlinge, D.
Abstract Ischaemic heart disease is the leading cause of death worldwide. The common denominator for plaques causing acute coronary syndrome (ACS) is lipid accumulation, either as a lipid core or lipid pools. An intracoronary imaging device to detect lipid‐rich plaques (LRPs) could therefore identify most of the plaques causing ACS and sudden death. Near‐infrared spectroscopy combined with intravascular ultrasound (NIRS‐IVUS) is a promising new intracoronary imaging method that is able to specifically quantify lipid accumulation measured as the lipid core burden index (LCBI). NIRS‐IVUS is highly specific for the identification of ST‐elevation myocardial infarction (STEMI) and non‐ST‐elevation myocardial infarction (NSTEMI) culprit plaques usually in the form of a circular LRP. NIRS‐IVUS may assist in defining the aetiology of coronary events. The effect of cholesterol‐lowering therapy on the lipid core can be measured in coronary plaques in patients, and NIRS‐IVUS may be a useful tool for drug development in phase II studies as a surrogate end‐point for future ACS. Plaques with a high LCBI have an increased risk of peri‐procedural events. NIRS‐IVUS can help to define the diameter and length of stents to avoid procedure‐related complications. Increased coronary LCBI predicts a higher risk of future cardiovascular events. Lipid core detection using NIRS may help to identify vulnerable plaques to treat them before they cause ACS or sudden death.